Chapter 3: Ethnic group classification in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (2016)
Keywords: blood quantum; crown policy; identity; self-identification

Indigenous Data Sovereignty: Toward an agenda - Kukutai, Tahu (ANU Press, 2016)
As the global ‘data revolution’ accelerates, how can the data rights and interests of indigenous peoples be secured? Premised on the United Nations Declaration on the Rights of Indigenous Peoples, this book argues that indigenous peoples have inherent and inalienable rights relating to the collection, ownership and application of data about them, and about their lifeways and territories. As the first book to focus on indigenous data sovereignty, it asks: what does data sovereignty mean for indigenous peoples, and how is it being used in their pursuit of self-determination? The varied group of mostly indigenous contributors theorise and conceptualise this fast-emerging field and present case studies that illustrate the challenges and opportunities involved. These range from indigenous communities grappling with issues of identity, governance and development, to national governments and NGOs seeking to formulate a response to indigenous demands for data ownership. While the book is focused on the CANZUS states of Canada, Australia, Aotearoa/New Zealand and the United States, much of the content and discussion will be of interest and practical value to a broader global audience.
Keywords: data; data sovereignty; indigenous data sovereignty

The field of Indigenous health and the role of colonisation and history - Axelsson, Per; Kukutai, Tahu; Kippen, Rebecca (Journal of Population Research, 2016)
Keywords: Inequity; colonisation; disparities; displacement; health; health outcomes

Here to stay: Reshaping the regions through mana Māori - Kukutai, Tahu; Simmonds, Naomi Beth; Ryks, John (Massey University Press, 2016)
Situated 65 kilometres south-east of Hamilton, Putāruru (population 3747 in the 2013 Census) is typical of the many farming service towns scattered across rural Aotearoa New Zealand. Bakeries, op shops, a sports bar and a farm equipment supplier occupy the main street. Unlike nearby Tirau, which transformed from a one-stop shop into a vibrant boutique village in the late 1990s, Putāruru township remains largely indistinguishable from other rural centres. There are few clues to the substantial farming-based and water-generated wealth that lies beyond the town.
Keywords: economic aspects; mana whenua; tino rangatiratanga

Statistics on indigenous peoples: International effort needed - Madden, Richard; Axelsson, Per; Kukutai, Tahu; Griffiths, Kalinda; Storm Mienna, Christina; Brown, Ngaire; Coleman, Clare; Ring, Ian (Statistical Journal of the IAOS, 2016)
In 2007, the UN General Assembly endorsed the United Nations Declaration on the Rights of Indigenous Peoples. In the following years, there has been a strong call from a range United Nations agencies and spokespersons for countries to act to improve their statistics relating to Indigenous peoples as part of their response to the Declaration. These calls have emphasised the need for a holistic approach, describing strengths and resilience of Indigenous peoples and not just a focus on gaps and disadvantage. National responses have been mixed and overall statistics remain inadequate. Signiﬁcantly, there has been no international statistical effort through the United Nations statistical structures to respond to the Declaration and the increasing array of calls for improved statistics. The United Nations Statistical Commission in particular has an array of mechanisms to study statistical needs and develop solutions across a broad international statistical agenda. It is time for countries to make a concerted effort to improve their own statistics on Indigenous peoples, and to insist that the Statistical Commission work in partnership with the Permanent Forum on Indigenous Issues and other stakeholders to lead a major international drive to improve statistics on and for Indigenous peoples.
Keywords: data; statistics